PENGARUH LINGKUNGAN KERJA, PENGETAHUAN DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI SELATAN - Indira Basalamah (AkMen JURNAL ILMIAH, 2016)
The purpose of this study were 1) to analyze the influence of the work environment, knowledge and discipline on the performance of employees of Regional Employment Board of South Sulawesi province, and 2) to analyze the most dominant variables affect the job performance of employees Regional Employment Board of South Sulawesi province. The analytical method used in this research is the method of multiple regression analysis. Data were obtained from the employees of the Regional Employment Board of South Sulawesi province. The research approach is causal explanatory approach. The results of this study show that: 1) the results of regression analysis showed that the work environment positive and significant effect on the performance of employees of Regional Employment Board of South Sulawesi province. This shows that with a good working environment in the work will obtain work performance of employees is also good while with a work environment that is low will generate work performance of employees is low, 2) the results of regression analysis showed that knowledge variable positive and significant effect on work performance employees of the Regional Employment Board of South Sulawesi province. From the results of this study indicate that the better knowledge, the better the job performance of employees Regional Employment Board of South Sulawesi province and is the most dominant variable influence on the performance of employees of Regional Employment Board of South Sulawesi province, and 3) the results of regression analysis showed that the variables labor discipline positive and significant effect on the performance of employees of Regional employment Board of South Sulawesi province. From the results of this study indicate that employees with high work performance can be explained because it has a high work discipline both in planning, implementing and evaluating a whole series of jobs in the Regional Employment Board of South Sulawesi province.